2019
DOI: 10.1080/19476337.2019.1613449
|View full text |Cite
|
Sign up to set email alerts
|

Effect of in vitro gastrointestinal digestion on the composition and bioactivity of anthocyanins in the fruits of cultivated Lycium ruthenicum Murray

Abstract: 2019) Effect of invitro gastrointestinal digestion on the composition and bioactivity of anthocyanins in the fruits of cultivated Lycium ruthenicum Murray, ABSTRACT The composition of anthocyanins in cultivated Lycium ruthenicum Murray (CLM) before and after in vitro gastrointestinal digestion was determined using an HPLC system coupled with an electrospray ionization-time of flight mass spectrometry. The antioxidant activity and α-glucosidase inhibition of the anthocyanins before and after digestion were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The results of the evaluation of the percentage of inhibition of the four prepared extracts on the activity of α-amylase were significantly different (p < 0.05) and are shown in Table 2. Wang et al [26] reported the same phenomenon in the inhibition of α-amylase in in vitro assay due to the content of anthocyanins of the fruits of cultivated Lycium ruthenicum Murray. WFE extracts had the highest percentage of inhibition of 70% at 25 mg/mL.…”
Section: Inhibition Assay Of α-Amylase and α-Glucosidasementioning
confidence: 67%
“…The results of the evaluation of the percentage of inhibition of the four prepared extracts on the activity of α-amylase were significantly different (p < 0.05) and are shown in Table 2. Wang et al [26] reported the same phenomenon in the inhibition of α-amylase in in vitro assay due to the content of anthocyanins of the fruits of cultivated Lycium ruthenicum Murray. WFE extracts had the highest percentage of inhibition of 70% at 25 mg/mL.…”
Section: Inhibition Assay Of α-Amylase and α-Glucosidasementioning
confidence: 67%
“…For instance, Birk et al reported a rapid degradation of octyl-β- d -glucopyranoside and glycosylated resveratrol to the parent aglycone in an in vitro Rumen Simulation System, within 30 min to 1 h . Conversion of the glycosylated forms of anthocyanins during in vitro gastrointestinal digestion into anthocyanidins has also been reported previously. , These previous results suggest that glycosylated compounds may be converted into parent aglycones during in vitro digestion, due to the acidic pH and/or enzymes present in the digestive fluids. Future work is needed to examine the specific mechanisms of the conversion reactions, as well as identification of any other molecules formed during this process, as all of this information will be critical to informing subsequent human health risk assessment of food crops contaminated with antibiotics.…”
Section: Results and Discussionmentioning
confidence: 97%
“…Currently, there are no reports describing the anti‐PL activity of this anthocyanin in scientific literature. However, it has been demonstrated that this compound could be hydrolyzed to produce aglycones by several digestive enzymes, including lipases [19] . This fact may suggest that highly glycosylated substrates such as petunidin‐3‐( cis ‐p‐coumaroyl)‐rutinoside‐5‐glucoside can be hydrolyzed by digestive enzymes.…”
Section: Resultsmentioning
confidence: 99%
“…However, it has been demonstrated that this compound could be hydrolyzed to produce aglycones by several digestive enzymes, including lipases. [19] This fact may suggest that highly glycosylated substrates such as petunidin-3-(cis-p-coumaroyl)-rutinoside-5glucoside can be hydrolyzed by digestive enzymes. For all anthocyanin assayed, IC 50 values were higher than those obtained for current drugs used as inhibitors of these enzymes (Table 2).…”
Section: Inhibitory Properties Of Snaf and Pure Anthocyanins On Targe...mentioning
confidence: 99%